Pattern of Kyai Parenting In Building Characterat Daarel Qolam 2 Islamic Boarding School Tangerang And La Tansa Mashiro Lebak Islamic Boarding School - Solihin, Solihin; Supiana, Supiana; Arifin, Bambang Samsul; Jamaludin, Dindin (Pusat Publikasi Nusantara, 2022)
Kyai Parenting Patterns in Building Character Daar El Qolam 2 Tangerang and La Tansa Mashiro Lebak. Both Daar El Qolam 2 and La Tansa Mashiro are Islamic Education Institutions with special characteristics. In implementing the kyai's upbringing, many things determine the formation of the character of the santri. Therefore, institutions try several ways to overcome ideal parenting to develop student character. This research tries to investigate; 1) Purpose of Kyai Parenting, 2) Kyai Parenting Program, 3) Implementation of Kyai Parenting, 4) Evaluation of Kyai Parenting, 5) Strengths and Weaknesses of Kyai Parenting, 6) Impact of Kyai Parenting. Educator or teacher theory, parenting style, and implementation of Kyai to build character. This research uses descriptive qualitative method with data analysis. Collecting data through observation, interviews and documentation studies. The research results show; 1) the upbringing of the kyai at the Daar el Qolam 2 Islamic boarding school and the La Tansa Mashiro Islamic boarding school is classified as good in terms of the system aspect, well-structured management, and the rules that exist in the Islamic boarding school 2) The kyai parenting program at Daarel Qolam 2 Islamic Boarding School and La Tansa Islamic Boarding School is to build character who masters various sciences 3) The implementation of the character development program for students at Daar el Qolam and La Tansa Mashiro Islamic Boarding Schools is going well in the aspect of mastering various sciences 4) Evaluation of kyai parenting patterns at Islamic Boarding Schools Qolam 2 and Islamic Boarding School La Tansa Mashiro is very good 5) The superiority factor at Daar el Qolam 2 Islamic Boarding School and La Tansa Mashiro Islamic Boarding School is in human resources, plus the teachers at both Islamic boarding schools live in the same environment or dormitory 6) The upbringing of the kyai of Daarel Qolam Islamic boarding school has an impact positive for character building.